Karakteristik Organoleptik dan Mutu Kimia Cookies Tepung Talas dengan Penambahan Bayam Brazil (Althernanthera sisso) - Abdi, Yenny Febriana Ramadhan; Suleman, Dininurilmi Putri; Darisna, Lufi Ayunda; Rochmah, Alfi Nur; Nadhilah, Dini; Zulfa, Fitriyah; Rizki, Prajwalita Rukmakharisma (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPA, 2025)
People's food consumption patterns tend to like snacks such as cookies. Dependence on used of flour in making cookies is now starting to be reduced the alternative ingredients from local food are needed instead. Taro flour is a type of flour made from local food is high in nutrition and can be used as a substitute for wheat flour. Apart from that, cookies also require the contribution of macro and micronutrients obtained from animal and plant foods. Brazilian spinach can be used as a source of micronutrients because it is high in vitamins and minerals. The aim of this research is to determine the organoleptic characteristics and chemical quality of cookies. The method used in this research used a completely randomized design with a comparison of wheat flour, taro flour and Brazilian spinach in 4 treatments with 3 repetitions including (F1 (100 g: 0 g: 0 g), F2 (85 g: 15 g: 10 g), F3 (85 g : 15 g : 20 g) and F4 (85 g : 15 g : 30 g). The data obtained will be analyzed using one-way ANOVA and followed by the DMRT test at the 5% level. The results showed that the addition of 20 g of Brazilian spinach and obtained chemical test results including a moisture content test of 3.22%, fat content of 21.18%, protein content of 7.81%, Fe content of 11.71 mg and the cookies that were preferred by the panelist had yellowish color, with a typical spinach aroma, slightly unpleasant, savory taste as well as a dense, crunchy texture not easily crushed. Keywords: Brazilian spinach, Cookies, Taro flour.